2011
DOI: 10.1186/1746-6148-7-79
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity-mortality and performance evaluation of Brahman calves from in vitro embryo production

Abstract: BackgroundThe use of bovine in vitro embryo production (IVP) increases the reproductive potential of genetically superior cows, enabling a larger scale of embryo production when compared with other biotechnologies. However, deleterious effects such as abnormal fetal growth, longer gestation period, increased birth weight, abortion, preterm birth and higher rates of neonatal mortality have been attributed to IVP. The aim of this study was to compare the influence of in vitro embryo production and artificial ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Parturitions in IVP-derived pregnancies are known to have a tendency to be more difficult than AI pregnancies [29,51,52,56]. In our study, three IVP pregnancies were considered difficult while all AI calving were evaluated as easy, not being statistically relevant.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Parturitions in IVP-derived pregnancies are known to have a tendency to be more difficult than AI pregnancies [29,51,52,56]. In our study, three IVP pregnancies were considered difficult while all AI calving were evaluated as easy, not being statistically relevant.…”
Section: Discussionmentioning
confidence: 89%
“…Gestation lengths are reported to be longer for IVP pregnancies in some studies [15,[47][48][49][50][51][52], but similar to AI in others [5,53]. It should be noted that the percentage of induced parturitions was higher in IVP (regardless of the RF or BSA supplementation) pregnancies than AI pregnancies (with a tendency to be significantly different), and those pregnancies lengths (n = 7) were not accounted for mean gestation length, which if it did, would probably contribute to an increase in the mean gestation length.…”
Section: Discussionmentioning
confidence: 98%
“…Calves born by NM showed lower BBW than those born by ET. Likewise, Pimenta-Oliveira et al [ 29 ], found differences in birth weight of the offspring between the IVP embryos and AI. Nonetheless, Lopes et al [ 30 ], compared the growth of calves born by ET with those from AI, and their results showed much similarity between groups in terms of pregnancy rates, gestation length and calves’ birth weight.…”
Section: Discussionmentioning
confidence: 96%
“…As with BBW and WBW, the average daily weight gain (ADG: NM 0.72; ET 0.92) was statistically associated with all the study variables. Effectively, Pimenta-Oliveira et al [ 29 ] found no differences in ADG between ET and AI. This effect could be due to a similar selection process for dams and bulls in both reproductive techniques, thus not affecting the weight of the offspring until weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Brazil is an important country for cattle breeding for milk and meat, having one of the largest herds in the world. Brazilian livestock production is characterised by large-scale extensive operations under grazing conditions using mainly natural mating or artificial insemination (AI) as reproductive strategies, although the use of in vitro embryo production (IVP) has increased each year for animals of high genetic value (Pimenta-Oliveira et al 2011). In contrast, there have only been a few studies of genetic diseases in the Brazilian cattle herd.…”
Section: Introductionmentioning
confidence: 99%